Nanohole-boosted electron transport between nanomaterials and bacteria as a concept for nano–bio interactions - Tonglei Shi (Nature Portfolio, 2021)
Nanomaterials have attracted attention as antibacterial agents and have several modes of action. Here, the authors report on 2D transition metal disulphide nanosheets with hole boosted electron donation/withdrawal for enhanced antibacterial and biofilm activity caused by electron damage.